Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
536x27-(825+219):18+153:152-42x3
=536x27-(825+219):18+151-16x3
=536x27-1044:18+15-16x3
=14472-58+15-48
=14414+15-48
=14429-48
=14381
\(\frac{11.3^{25}.3^7-9^{15}}{\left(2.3^{14}\right)^2}=\frac{11.3^{32}-\left(3^2\right)^{15}}{2^2.\left(3^{14}\right)^2}=\frac{11.3^{32}-3^{30}}{4.3^{28}}=\frac{3^{30}.\left(11.3^2-1\right)}{4.3^{28}}=\frac{3^2.98}{4}=\frac{9.98}{4}=\frac{882}{4}=\frac{441}{2}\)
2.
\(\left(1+2+3+...+100\right)\cdot\left(1^2+2^2+3^2+...+10^2\right)\cdot\left(65\cdot111-13\cdot15\cdot37\right)\\ =\left(1+2+3+...+100\right)\cdot\left(1^2+2^2+3^2+...+10^2\right)\cdot\left(65\cdot111-13\cdot5\cdot3\cdot37\right)\\=\left(1+2+3+...+100\right)\cdot\left(1^2+2^2+3^2+...+10^2\right)\cdot\left[65\cdot111-\left(13\cdot5\right)\cdot\left(3\cdot37\right)\right]\\ =\left(1+2+3+...+100\right)\cdot\left(1^2+2^2+3^2+...+10^2\right)\cdot\left[65\cdot111-65\cdot111\right]\\ =\left(1+2+3+...+100\right)\cdot\left(1^2+2^2+3^2+...+10^2\right)\cdot0\\ =0\)
2^18 : 2^15 + 3^2 * 2^3 -7
= 2^3 + 3^2 * 2^3 -7
= 8+9*8-7
= 8+72-7
=80-7
=73
2^18:2^15+3^2.2^3-7
=2^3+3^2.2^3-7
=2^3.1+3^2.2^3-7
=2^3.(9+1)-7
=8.10-7
=80-7
=73
CHÚC BN HC TỐT